Fiscal Policy Rules for Oil-Producing Countries : A Welfare-Based Assessment - Maliszewski, Wojciech (IMF Working Papers; Working Paper, 2009)
The paper presents numerical simulations of various fiscal rules for oil-producing countries. Welfare implications are sensitive to the choice of the social welfare function, initial conditions, and non-oil growth prospects. The distribution of non-oil wealth is important for countries with relatively low oil reserves. Corrections for adjustment costs and uncertainty with respect to oil prices should be applied carefully. While avoiding sharp changes in the fiscal policy stance may be appealing, it is not necessarily optimal if the initial position is unsustainable. Ad hoc rules are shown to perform poorly. The analysis abstracts from several issues critical for developing a practical policy advice and should not be treated as a complete framework.